Iron citrate Synthesit: Impact on blood parameters in non-iron deficient models - Kusnir, Patrik; Bulgin, Dmitry; Baig, Shahbaz (Edelweiss Applied Science and Technology, 2024)
Iron's significance extends beyond treating anemia, impacting various disorders. However, studies on iron-fortified diets in healthy subjects are limited. To evaluate the effects of Synthesit iron citrate on biochemical, hematological parameters, and body weight in aged rhesus macaques, and its safety in SHK-line mice. An experimental study involved SHK mice and rhesus macaques receiving Synthesit iron citrate, with blood parameters, histology, hematopoietic stem cells, and biochemistry monitored over 30 days (14 mice) and six weeks (8 macaques). The study shows increased hematopoietic cell types and mitosis index, with significant increases in Myelokaryocyte count (32.4%), megakaryocyte count (3.7-fold), myeloblast count (1.7-fold), mononuclear cell count (2.5-fold), erythroblast count (4-fold), and reticulocytes (13.3%). In macaques, supplementation initially reduced erythrocyte count, followed by recovery, while thrombocyte count increased initially but decreased post-supplementation. Leukocyte analysis showed varied responses, with a decrease in monocyte and lymphocyte but an increase in neutrophil percentage. Biochemical analyses revealed improvements in glucose (baseline: 4.36 ± 0.32 mmol/l vs day 43: 3.30 ± 1.06 mmol/l), cholesterol (baseline: 4.563 ± 0.799 mmol/l vs day 29: 2.84 ± 0.88 mmol/l), and triglyceride levels (baseline: 1.49 ± 0.63 mmol/l vs day 29: 0.70 ± 0.34 mmol/l). The novel study reveals the effects of iron citrate synthesis in non-iron deficient models into the blood parameters which has metabolic potential. In conclusion, Synthesit® iron citrate supplementation exhibits promising effects on hematopoiesis and metabolic parameters in murine and primate models.